Sustainable Architecture: the Eco-Efficiency Earth Construction - Sposito, Sposito; Scalisi, Francesca (European Journal of Sustainable Development, 2017)
The appropriate choice of building materials can contribute decisively to reduce the energy consumption of the building sector. The increasing worries for the environmental impact of construction materials is witnessed by a lot of studies The mentioned worries has brought again the attention towards natural materials. The use of more sustainable construction materials and construction techniques represent a major contribution to the eco-efficiency of the construction industry and thus to a more sustainable development. Within this frame the renewed interest for a natural material such as the rammed earth is included; the interest has been in continuous growth from the 80s till today. The rammed earth’s advantages regarding these requirements are evident: the resource is available in great amounts, the energy needed for extraction, transformation and production of the material is very low and it is a wholly recyclable material. Besides these benefits, the interest is due to its high thermal inertia and hard hygroscopic properties. Keywords: earth construction, sustainability, architecture